Ukama Ustawi's Learning Alliance: summary and key insights - Beukman, R.; Nohayi, Ngowenani; Victor, M.; Mahuku, G.; Jacobs-Mata, Inga; Ires, Idil (International Water Management Institute (IWMI), 2023)
Knowledge management and sharing is essential for agricultural development, fostering the exchange of valuable information and innovative practices among researchers, farmers, and extension officers. Recognising this, regional initiatives such as Ukama Ustawi (UU) play a critical role in ensuring that research findings are not confined to academic journals but are made accessible to those who need them the most. UU’s Learning Alliance, led by the International Livestock Research Institute (ILRI) and the International Water Management Institute (IWMI), facilitated a joint session at the Africa Agribusiness & Science Week (AASW8) in Durban, South Africa. The collaboration involved partners such as the Centre for Coordination of Agricultural Research and Development for Southern Africa (CCARDESA), Forum on Agriculture Research for Africa (FARA), and Association for Strengthening Agricultural Research in Eastern and Central Africa (ASARECA). The session was part of a broader workshop focused on Knowledge Management and Learning (KML). UUs Learning Alliance session was therefore aimed at achieving three key objectives: highlighting the Alliance's strategic focus, emphasising its value proposition, and sought to strengthen the relationship between CGIAR research and regional as well as national research organizations. Discussions underlined the urgency of overcoming barriers in information flow among stakeholders, with a particular focus on the Learning Alliance's mission to curate, repackage, and share knowledge on maize mix-based farming systems in East and Southern Africa (ESA). The Alliance aspires to foster connections between CGIAR and local research organizations while providing National Agricultural Research Organization (NARO) and Agricultural Research Organizations (ARO) partners with opportunities to engage, test, and innovate. The report emphasises the critical role of UU in defining specific KML activities tailored to their focus areas. This strategic approach aims to build capacities, generate relevant Knowledge Products (KPs), and facilitate knowledge uptake, with the goal of driving impact and sustainability within the agricultural landscape of East and Southern Africa.